IMPROVING THE STUDENTS’ VOCABULARY ACHIEVEMENT BY USING PICTURES - Ammatunnur Siddiqa; Amrin Saragih (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2012)
This study attempts to increase students’ vocabulary achievement by using pictures. This study is conducted by using Classroom Action Research. This study was conducted as the first grade students of SMP Nurul Hasannah Medan. One class from four classes was selected as the subject of this research. The number of the subject of the reseearch was 38 students. The class taught by using interview sheet and observation sheet. The quantitative data were collected by giving multiple choice tests counting the mean of the students. The result of the research shows that the mean of the second cycle (77.29%) is higher than the mean of the first cycle(72.71%) and pre test (67.14%). Based on the observation sheet, interview sheet, questionnaire sheet and diary notes, the students were more active and enthusiastic during the teaching and learning process in the second cycle than in the first cycle. Key Words:  Vocabulary, Pictures